Germany : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
This report reviews observance of standards and codes on the Financial Action Task Force (FATF) Recommendations for antimoney laundering and combating the financing of terrorism (AML/CFT) for Germany. The report reveals that the AML/CFT framework is not fully in line with the FATF Recommendations. There are weaknesses in the legal framework and in sanctioning for noncompliance with AML/CFT requirements. German authorities regularly use a broad range of legal procedures to seize, confiscate, and forfeit property, but they confiscate and forfeit a lot less property than the courts issue orders for.